Effect of ascorbic acid on seed germination of three halophytic grass species under saline conditions. (29th August 2012) - Zehra, A.; Shaikh, F.; Ansari, R.; Gul, B.; Khan, M. A.
Abstract Grasses on the Pakistani coast are moderately to highly salt tolerant and have potential for utilization as a cash crop. This study was designed to determine whether seed germination of three halophytic grasses (Phragmites karka, Dichanthium annulatum and Eragrostis ciliaris) could be improved by exogenous application of ascorbic acid (AsA) under saline conditions. Seeds of P. karka were germinated in varying concentrations of NaCl and AsA under different temperature regimes, and seeds of Dichanthium annulatum and Eragrostis ciliaris were germinated at optimal temperatures only. In P. karka, concentrations of AsA (5 and 10 mM) alleviated the salinity effects better at cooler and moderate thermo‐periods, whereas higher concentrations (20 mM of AsA) failed to improve germination under all temperature regimes. AsA was ineffective at a warmer thermo‐period (25/35°C). The rate of germination also increased at all thermo‐periods with the application of AsA except at 25/35°C under saline conditions. Application of AsA improved the germination of E. ciliaris seeds under saline conditions but was inhibitory for D. annulatum in comparison with the untreated control. The rate of germination followed the similar pattern as that of seed germination. Results indicate that AsA has the ability to partially alleviate the effect of salinity on seed germination of some grass species under optimal temperature regime.